(untitled) (International Journal of Engineering and Computer Science, 2018)
Energy is a valuable input in all sectors of any country’s economy. Today most of the countries draw its energy need using a variety of sources. Out of all these sources wind energy is an efficient and economically viable energy resource which is safe and has no side effects on the environment. Attempts are being made to develop low cost wind mills which can be used for generation of electricity and irrigation purposes. Therefore this paper presents various causes and remedies so that the usage of wind turbine can be assured as safe and free from causing any sort of harmful impact on the surroundings as well as the environment.